Ответы и объяснения

2013-09-19T12:13:18+04:00
(x^{3}+1)-(12x^{2}+12x) \geq 0
(x+1)(x^{2}-x+1)-12x(x+1) \geq 0
(x+1)(x^{2}-x+1-12x) \geq 0
(x+1)(x^{2}-13x+1) \geq 0
Разложим на множители выражение, стоящее во 2-х скобках
x^{2}-13x+1=0
D = (-13)^{2}-4*1*1=165
x_{1}=\frac{13-\sqrt{165}}{2}\approx\frac{13-12,8}{2}=0,1
x_{2}=\frac{13+\sqrt{165}}{2}\approx\frac{13+12,8}{2}=12,9

(x+1)(x-\frac{13-\sqrt{165}}{2})(x-\frac{13+\sqrt{165}}{2}) \geq 0
С помощью метода интервалов находим ответ:
x \in [-1;\frac{13-\sqrt{165}}{2}] \cup [\frac{13+\sqrt{165}}{2}; +\infty)